2019
DOI: 10.3390/ijerph16244985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Faint Road Traffic Noise Mixed in Birdsong on the Perceived Restorativeness and Listeners’ Physiological Response: An Exploratory Study

Abstract: Many studies have reported that natural sounds (e.g., birdsong) are more restorative than urban noise. These studies have used physiological and psychological indicators, such as the skin conductance level (SCL) and the Perceived Restorativeness Scale (PRS), to evaluate the restorative effect of natural sounds. However, the effect of faint background noise mixed with birdsong on the restorativeness of birdsong has not been described yet. In the current experiment, we examined whether traffic noise affects the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Soundscapes are one of the main elements of restorative landscape design and have an important recreational value, and from a health perspective sound perception can be used as an enhancement tool for the human experience [18]. It has been shown that natural sounds such as birdsong are preferred to relieve stress, reduce anxiety and agitation and contribute to emotional recovery, and their restorative effects are supported by physiological indicators such as skin conductance level, heart rate and heart rate variability [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Soundscapes are one of the main elements of restorative landscape design and have an important recreational value, and from a health perspective sound perception can be used as an enhancement tool for the human experience [18]. It has been shown that natural sounds such as birdsong are preferred to relieve stress, reduce anxiety and agitation and contribute to emotional recovery, and their restorative effects are supported by physiological indicators such as skin conductance level, heart rate and heart rate variability [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, by assessing the combined effect of beneficial and non-beneficial sounds, we could demonstrate that increasing perceptions of traffic volume undermined the beneficial effects of bird pleasantness. Recently, Suko et al (2019) found that faint levels of traffic noise among birdsongs resulted in significantly less physiological restoration than birdsongs without traffic noise. However, with respect to perceived restorativeness, the same study did not find any significant differences with or without the traffic noise amongst bird songs.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic sounds such as traffic noise may constrain restoration benefits associated with bird sounds. Although Suko et al (2019) found that bird songs with and without low traffic noise displayed no significant difference between perceived restorativeness scores, they did not examine the effect of varying levels of traffic noise. We hypothesise that as traffic noise is more strongly perceived among bird sounds, the beneficial effects of these soundscapes will be increasingly constrained.…”
Section: Theoretical Frameworkmentioning
confidence: 95%
See 2 more Smart Citations